2023
DOI: 10.5539/ijef.v15n4p47
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Study on the Nexus of Economic Growth and Renewable Energy in Brazil

Abstract: The nexus between economic growth and energy consumption is essential in energy economics and economic development literature. The recent urgency in accelerating the decarbonization processes of economies has enhanced relevance to analyzing this empirical relationship in the face of technological advances, regulatory changes, and the expanding uptake of renewable energy technologies worldwide. This article presents a bibliometric analysis of the literature on economic growth, energy consumption, and renewable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In other bibliometric studies, China is identified as the country with the highest number of publications on renewable energy [64,66,67] or within the top three [23,31,62,63,65]. Considering only the number of articles, the study also identified that the articles found were mainly of Chinese and Italian origin (Figure 6).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In other bibliometric studies, China is identified as the country with the highest number of publications on renewable energy [64,66,67] or within the top three [23,31,62,63,65]. Considering only the number of articles, the study also identified that the articles found were mainly of Chinese and Italian origin (Figure 6).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, regarding the nationality of the journals, it is evident that most of them are from the United Kingdom (7 of the top 10), Switzerland (2), and the Netherlands. In other bibliometric studies, the journal Energies also leads in the scientific contribution to renewable energies or at least in the top 10 journals [31,63,64]; Energy is also among the top 10 journals [23,66]. As for the institutions with the highest scientific production, the Technical University of Denmark and Aalborg University were identified as the leaders in this field, both of Danish origin (Table 2).…”
Section: Discussionmentioning
confidence: 94%